Par dažiem neskaidras cilmes Latvijas hidronīmiem - Balode, Laimute (Baltistica, 1996)
ON SOME LATVIAN HYDRONYMS OF UNCLEAR ORIGIN This article deals with some interesting Latvian hydronyms of unclear origin: Latvian lake-names Amardas ezers, Āzdrims2, Davilnītis, Kladācis, Kurēlis and their possible different variants, etc. There are proposed some new etymological and derivational hypotheses. The author also examines some Latvian hydronyms mentioned in classical onomastic sources which most credibly are misprint: Reislais ezers, Skugņu ezers.